The Analysis of Population Structure of Mud Crab (Scylla serrata) in The Mangrove Forest Area of Bagek Kembar, West Lombok - Hilmi, Masnayati; Karnan, Karnan; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Scylla serrata is one of the species included in the mangrove forest ecosystem which has high economic value for human life. Seeing that mud crabs have high economic potential both domestically and abroad with a fairly high level of demand and abundant availability of catches in nature, concerns arise about the condition of their population. This research aims to determine the population structure of mangrove crabs in the Bagek Kembar Mangrove Forest Area, West Lombok. The method used is purposive sampling. Sampling was carried out at 3 stations representing the entire research location area, namely on the seafront, in the middle and farthest from the arena facing the sea. Each station has its own characteristics. The distance between stations is 50 m. Each station is installed 6 folding trap with a distance between trap 10 m. The length, width, and high size are 50 cm, 30 cm, and 15 cm respectively. This tools are completed by 3 mm mesh size. The results of the research showed that the carapace length of male and female mud crabs that were mostly caught was in the 3 – 4.5 cm and 2.5 – 4.0 cm classes. The carapace width of male and female mud crabs most often caught is in the range of 4.4 – 6.5 cm and 3.5 – 5.5 cm. And the weight of the most commonly caught male and female mud crabs was in the class range of 11.39 – 111.5 grams and 13.77 – 74.5 grams. This research concludes that mangrove crabs that live in the Bagek Kembar Mangrove Forest Area, West Lombok, based on gender, carapace length, carapace width and body weight, are dominated by juveniles. Only a limited number reach catch size.